Executive Authority Between the Political System of France and Kurdistan Region- Iraq : (Comparative Research) - Barzan Jawhar Sadeq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
From Aristotle’s time up to now comparative politics has been one of the major political science fields and has had a significant impact on the progress of various political systems. Founding a political system is related to some factors, one of them is the effect of a powerful state to composition of a new political system in another region. Kurdistan region is at the beginning of fixing the nature of its political system. There many similarities and less differences between both political systems (France & Kurdistan region), this research depends on comparative method deals with comparation executive powers of both countries. Despite Kurdistan region being a de facto for three decades, some basic laws have been practiced from founding the region that are shaped like constitution which could be used as comparative fields to compare with other political systems. Focusing on those two mentioned mechanisms and depending on Iraqi constitution according to Kurdistan regions authority, we have compared France and Kurdistan region political systems. Through focusing on both political systems, it seems that the authorities of both presidents are in common in terms of foreign and domestic policy. Both presidents are the head of army forces, executive authority and other presidency authorities, except the other commons between their ministry councils that the research analyzes by depending on law and constitution articles.